Comparison of long-term outcome in patients with calcified stenosis treated with intravascular lithotripsy or with modified balloon angioplasty: a propensity score-adjusted study - Leick, Jürgen; Rheude, Tobias; Denne, Michael; Cassese, Salvatore; Kastrati, Adnan; Hauptmann, Felix; Gehrig, Thomas; Kuna, Constantin; Lindner, Michael; Lauterbach, Michael; Werner, Nikos (Frontiers in Cardiovascular Medicine, 2023)
Background: The aim of this two-center, all-comers registry was to compare the effectiveness and safety of intravascular lithotripsy (IVL) to that of modified balloon angioplasty (MB). MB angioplasty using a cutting or scoring balloon is commonly used in patients with calcified coronary arteries. IVL is a new technology for lesion preparation. This is the first study to compare MB with IVL. Methods: The cohort included all patients treated by MB angioplasty or IVL between 2019 and 2021. The primary endpoint was strategy success (<20% residual stenosis). The secondary endpoint was long-term safety outcomes (cardiac death, acute myocardial infarction (AMI), target lesion failure/revascularization (TVR). Quantitative coronary angiography (QCA) was performed in all patients. Primary and secondary endpoints were compared using inverse probability of treatment weighting (IPTW) for treatment effect estimation. Results: A total of n=86 patients were treated by IVL and n=92 patients by MB angioplasty. The primary endpoint was reached in 152 patients (85.4%). Patients in the IVL group had less residual stenosis (5.8% vs. 22.8%; p=0.001) in QCA. Weighted multivariable regression analysis revealed that IVL had a significant positive effect on reaching the primary endpoint of strategy success (odds ratio [OR] 24.58; 95% confidence interval [95%CI] 7.40-101.86; p=0.001). In addition, severe calcification was shown to result in a lower probability of achieving the primary endpoint (OR 0.08; 95%CI 0.02-0.24; p=0.001). During the follow-up period (450 days) there was no difference in cardiovascular mortality rate (IVL (n=5) 2.8% vs. MB (n=3) 1.7%; p=0.129). Patients with unstable angina at the time of the index procedure had the highest probability of cardiovascular death (hazard ratio (HR) 7.136; 95%CI 1.248-40.802; p=0.027). No differences were found in long-term rates of AMI (IVL 1.7% vs. MB 2.8%; p=0.399; IVL HR 2.73; 95%CI 0.4-17.0; p=0.281) or TVR (IVL 5.6% vs. MB 9%; p=0.186; IVL HR 0.78; 95%CI 0.277-2.166; p=0.626). Conclusion: IVL leads to a significantly better angiographic intervention outcome compared to MB angioplasty in our cohort. During long-term follow-up, no differences in cardiovascular mortality, rate of acute myocardial infarction, or target lesion failure/revascularization were observed.